HOX transcript antisense intergenic RNA is differentially expressed in hypertrophic scar tissues and regulates the biological function of scar fibroblasts through sponging miR-30a-5p - Yong Song; Yi Wang; Minjian Chen; Zhenni Wei (Wolters Kluwer Medknow Publications, 2023)
Background: The pathogenesis of hypertrophic scars (HS) is complex and unclear. It is of great importance to investigate the formation mechanism of HS at the gene level, find new targets for gene therapy, and establish effective prevention strategies for the formation of HS. Objectives: The study explored the expression pattern of HOX transcript antisense intergenic RNA (HOTAIR) and miR-30a-5p in scar tissues of HS patients and investigated their regulatory role in fibroblast function. Methods: Forty HS patients were recruited, and their scar tissues and adjacent normal skin tissues were collected. Fibroblasts were extracted from these tissues. The quantitative reverse transcription-polymerase chain reaction was used for the mRNA measurement. The CCK-8 and transwell assay were applied for cell proliferation and migration assessment. Luciferase reporter assay was done to verify the target gene of HOTAIR. Results: Elevated HOTAIR and decreased miR-30a-5p were measured in both scar tissues and scar fibroblasts, and their levels were negatively correlated. HOTAIR acted as the sponge of miR-30a-5p. HOTAIR knockdown inhibited fibroblast proliferation, migration, and the expression of collagen synthesis-related proteins (procollagen, alpha-smooth muscle actin, and collagen I), but these functions were abolished by miR-30a-5p downregulation. Conclusion: HS patients owned elevated HOTAIR and decreased miR-30a-5p. HOTAIR knockdown can inhibit the proliferation, migration, and collagen synthesis of scar fibroblasts by negatively regulating the expression of miR-30a-5p.